Influences of Climate on Phyllosphere Endophytic Bacterial Communities of Wild Poplar - Firrincieli, Andrea; Khorasani, Mahsa; Frank, A. Carolin; Doty, Sharon Lafferty (Frontiers in Plant Science, 2020)
Plant-associated microbial communities play a central role in the plant response to biotic and abiotic stimuli, improving plant fitness under challenging growing conditions. Many studies have focused on the characterization of changes in abundance and composition of root-associated microbial communities as a consequence of the plant response to abiotic factors such as altered soil nutrients and drought. However, changes in composition in response to abiotic factors are still poorly understood concerning the endophytic community associated to the phyllosphere, the above-ground plant tissues. In the present study, we applied high-throughput 16S rDNA gene sequencing of the phyllosphere endophytic bacterial communities colonizing wild Populus trichocarpa (black cottonwood) plants growing in native, nutrient-limited environments characterized by hot-dry (xeric) riparian zones (Yakima River, WA), riparian zones with mid hot-dry (Tieton and Teanaway Rivers, WA) and moist (mesic) climates (Snoqualmie, Skykomish and Skagit Rivers, WA). From sequencing data, 587 Amplicon Sequence Variants (ASV) were identified. Surprisingly, our data show that a core microbiome could be found in phyllosphere-associated endophytic communities in trees growing on opposite sides of the Cascades Mountain Range. Like in other studies, the core microbiome was dominated by relatively few ASV whose taxonomic affiliation was restricted to Pseudomonadaceae (40% to 80%) and Enterobacteriaceae (17% to 60%) which dominated all host individuals. Alpha-diversity measures indicated that plants colonizing hot-dry environments showed a lower diversity than those from mid hot-dry and moist climates. Beta-diversity measures showed that bacterial composition was significantly different across sampling sites. Accordingly, we found that specific ASV affiliated to Pseudomonadaceae and Enterobacteriaceae were significantly more abundant in the phyllosphere endophytic community colonizing plants adapted to the xeric environment. In summary, this study highlights that sampling site is the major driver of variation and that only few ASV showed a distribution that significantly correlated to climate variables.